Enhance Productivity In The Garment Industry Through A Modified Value Stream Mapping Approach - Mudzakkir, Fajar; Alamsjah, Firdaus (INTECOMS: Journal of Information Technology and Computer Science, 2024)
The objective of this study is to overcome problems that occur in the garment industry, the company has tried to develop an agile system to increase productivity in this industry. The garment company that focusses on the production of woven bottoms and outerwear, noted that women's woven bottoms products have the highest demand throughout 2022. However, the company was unable to meet Brand demand of 3.5%. Production data shows defects in products, low quality raw materials, and unstable production processes. A modified Value Stream Mapping (VSM) methodology is use to consider all aspects of production. The results of traditional VSM and Value Stream Analysis Tools (VALSAT) analysis include current state and future state, identification of value added and non-value-added elements during the production process, as well as setting priorities to reduce waste in the production process, especially in inventory (19%), defective parts (17%), and transportation (15%). Based on the VALSAT matrix, Process Activity Mapping (33.5%), Supply Chain Response Matrix (21.6%), and Demand Amplification Mapping (15.3%) were obtained. The findings of this research are Pilot Run, which succeeded in becoming an agile and reliable system during the production process. Through the application of the methodology combined with VSM the results have improved compared to the traditional VSM method. This proves that this method is effective in overcoming takt time, cycle time, man power, and value-added ratio. Limitations of this research were also discussed, including that this research only focused on women's woven bottom products only on the production workflow. Kata Kunci: Agile System, Enhance Productivity, Garment Manufacturing, Lean Manufacturing, Value Stream Mapping.